Competency Gaps and Human Resource Structures in the Musrenbang: A Logic Model Perspective - Fitriani Abdullah; Ade Irma; Mohammad Rusli Syuaib; Rezka Fahmi Tiara B; Nirmala Apsari; Adelheid Sabuna; Muhamad Rivai Rahawarin (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
This study evaluates the quality of apparatus human resources in facilitating the Development Planning Deliberation (Musrenbang) in Ampelgading District, Malang Regency, using a Logic Model approach. This qualitative evaluative case study integrates an institutional capacity framework focusing on the human resources, organization, and task network dimensions with the Logic Model framework. Data were collected through in-depth interviews with informants drawn from district apparatus, the regional planning agency (Bappeda), village facilitators, and village governments, complemented by non-participant observation and document analysis of the Musrenbang process. The findings reveal a systemic human resource deficit: most of the structural positions that underpin Musrenbang remain vacant, including core functions such as the definitive District Head, the Head of the Planning Subdivision, and the Head of the Development Section. Apparatus facilitation competence is weak owing to the absence of technical guidance in recent years and limited mastery of the regional planning information system (SIPD). Inter-actor coordination rests on fragile informal channels. The study identifies bottlenecks at the resources–activities and activities–output transitions as the root cause of the failure to convert community aspirations. The resulting strategic design focuses on developing apparatus human resource capacity through continuous technical guidance, the appointment of permanent facilitators, and advocacy for filling strategic positions.